Modeling and simulation in Python : an introduction for scientists and engineers - Downey, Allen (No Starch Press, Inc., 2023)
"Teaches the art of describing and simulating real-world systems using Python. Learn to model discrete systems, like a bike-sharing network, as well as first-order systems, like a coffee cup as it cools down, and second-order systems, like projectiles moving through space. Each chapter features hands-on examples and exercises"--